The Impact of Community Dental and Oral Health Services During the Covid-19 Pandemic in Indonesia - Pindobilowo; Fauziah M Asim; Dwi Ariani; Margaretha Herawati (Formosa Journal of Sustainable Research, 2023)
Based on WHO data, the number of doctors who died from COVID-19 was 545 people, while there were 46 dentists. As a result, dental practice has become a problem during the COVID-19 pandemic. Several solutions were produced to solve this problem, namely switching to non-aerosol procedures. Purpose: to conduct a literature review that examines the impact of community dental and oral health services during the COVID-19 pandemic. Method: this literature study uses the narrative review method by analyzing various journals from the PubMed, EBSCO and Google Scholar online databases related to community dental and oral health services during the COVID-19 pandemic. Conclusion: During the COVID-19 pandemic, treatment at the dentist's clinic was carried out with very strict health protocols to prevent the spread of the virus